Pengaruh Penguatan dalam Membentuk Motivasi Belajar Siswa di Sekolah - Ainun, Ainun maulidya; Hasanah, Nofiatun; Kumullah, Rohimah (Jurnal Educazione : Jurnal Pendidikan, Pembelajaran dan Bimbingan dan konseling, 2023)
Learning motivation is a key factor in the success of student learning at school. This study aims to examine the effect of reinforcement on students' learning motivation at school. This study uses library research and literature study methods, namely research that is the object of study using library data, analyzing journals, books, and studying previous research. This research provides recommendations for teachers and schools to pay attention to the use of reinforcement strategies in supporting student learning motivation. Teachers can provide constructive feedback, reward student achievements, and provide consistent positive encouragement to maintain and increase student learning motivation. Schools can support these efforts by creating policies and environments that support the application of reinforcement in the learning process